CONNECTIONS OF TRANSVERSAL VOLUMES OF THE UPPER AND LOWER JAW AND SAGITTAL CHARACTERISTICS OF THE DENTAL ARCH WITH ODONTOMETRIC AND CEPHALOMETRIC INDICATORS OF YOUTH-BRACHYCEPHALS WITH ORTHOGNATIC BITE - Маrchenko А.V. (World of Medicine and Biology, 2018)
The article describes and analyzes the correlation of computer-tomographic characteristics of dental arcs with odontometric and cephalometric indices of youth-brachycephals with orthognathic bite. Relative majority of predominantly direct mean forces, correlations of linear sizes necessary for constructing the correct form of the dental arch with the size of the teeth and the cephalometric indices in the brachycephalic males are established with the parameters of the maxillary dental arch in the sagittal plane (43.0%), and the smallest - with the parameters of the maxillary dental arcs in the vertical plane (24.4%). With the transversal dimensions of the upper and lower jaw, the relative number of such correlations is 32.3%. The greatest number of correlations of the size of the teeth with transversal dimensions of the upper and lower jaw are established with mesiodistal (53.5% of the total number of links between these indices) and vestibular-tongue (50.7%) size of the crowns of the teeth and with the width of the dentin-enamel border in the vestibular-tongue direction (54.2%); with the parameters of the maxillary dental arch in the sagittal plane - almost similar distribution is maintained (80.6% with mesiodistal dimensions of crowns of teeth, 83.3% with vestibular-tongue dimensions of crowns of teeth, 72.2% with width of dentin-enamel border in vestibular-tongue direction, 72.2% with the width of the dentin-enamel border in the mesiodistal direction); with the parameters of the maxillary dental arc in the vertical plane there is a completely different distribution - the greatest number of correlations is established only with the width of the dentin-enamel border in the vestibular-tongue direction (38.9%) and with the cephalometric indices (34.3%).